KARAKTERISTIK FISIK SEDIAAN FOOT SANITIZER SPRAY KOMBINASI EKSTRAK BIJI KOPI (Coffea) DAN RIMPANG JAHE (Zingiber officinale) DENGAN VARISASI KECEPATAN DAN WAKTU PENGADUKAN - Wilda Amananti; Aldi Budi Riyanta (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
Foot odor is a common body odor problem. The smell of feet makes oneself and people around uncomfortable, the smell of feet can be eliminated by washing the foot using soap, using a tabun powder. However, the foot wash using soap or powder is assessed less practical. Footsanitizer Spray is a new innovation of foot odor relievers that are practical and efficient use. Stirring process will affect product quality especially particle size distribution. So in this study aims to assess the effect of speed and time stirring of physical characteristics of the preparation of the foot sanitizer spray. In this research has been done variation of speed and stirring time, variation of stirring speed is done by varying the stirring speed at 300 rpm, 500 rpm and 700 rpm. Variation in stirring time is done by varying the stirring time for 1 hour, 2 hours and 3 hours. From the results of this research can be concluded that coffee beans extract and ginger rhizome can be used as a spray footsanitizer. And the greater the speed of the mixing form of the Footsanitizer spray the more cloudy and the viscosity value and type weight is getting bigger. The longer the stirring also leads to greater viscosity and density values.